A Review on Chip Formation Characteristics Under Dry and Flood Cutting - Ungku, Haiqal (Research Progress in Mechanical and Manufacturing Engineering, 2022)
In this new globalization era, machine manufacturing has been developed too much. The purpose of this study is to review the chip formation in order to get desirable chip whether in dry cutting or flood cutting by using AISI 1045. Following the objective which to review the relation between machining parameters and chip pattern and to clarify the tool wear pattern with the reason of wear in dry and flood cutting. From the literature study that has been conducted by using repositories database, chip formation in each cutting style has been analysed.More than fifty articles were used in the analysis process. The parameter that has been set for this review is the cutting speed, cutting depths and rake angle. All the parameter result in this study has been recorded in two cutting style which is dry cutting and flood cutting. All the tool wear and tool wear reason in between two cutting styles has been recorded. Therefore, this research can be done to fulfil all the industries requirement in each product such as good surface finish, good accuracy and saving cost.